KONSEP ZONA KAWASAN SITUS SEJARAH GAMPONG PANDE BANDA ACEH - Ira Dama Yanti; Izziah Izziah; Muhammad Isya (Prodi Magister Teknik Sipil Unsyiah, 2018)
Based on the Banda Aceh Heritage City Action Plan (2012), Banda Aceh is one of 48 Cities / Districts involved in the Indonesian Heritage City Network (JKPI), participating in the Planning and Preservation of Heritage City Program (P3KP). In the draft of Qanun Banda Aceh No. 4/2009 on Urban Planning of Banda Aceh City in 2009-2029 in Article 49 section 5 Gampong Pande is designated as protected area, because there is Kandang XII tomb and also developed as a tourist area of history as mentioned in article 58 section 3. Some part of the area have been lost due to coastal erosion that occurred several decades ago. In addition, Gampong Pande is one of the worst affected by the tsunami that occurred on 26 December 2004. Historical buildings and other sites have been destroyed and lost by the tsunami. Furthermore, this historic area received less attention and care from the government. The problems in this study is what are the development characteristics (design guidelines) and the concept of the zone of the historical site area of Gampong Pande? The purpose of this study is to as producing design guidelines and the concept of zone of historical sites of Gampong Pande. The method used in this study is qualitative descriptive. The analysis of this study describes the theory of the urban design approach theory that proposedby Roger Trancik about figure ground, linkage, and place. The results of this study are expected to provide recommendations to the government related to the development of Gampong Pande as part of Heritage City in Banda Aceh. The results of the study has found some objects of cultural heritage based on interviews and literatures study. The community participated in preserving the cultural heritage of Gampong Pande. Many location points of cultural heritage were found as well as the discovery of cultural heritage objects in Gampong Pande.